2007
DOI: 10.1088/0022-3727/40/17/033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microstructure and crystallinity on the photocatalytic activity of TiO2thin films deposited by dc magnetron sputtering

Abstract: TiO2 thin films were deposited by dc magnetron sputtering from sub-stoichiometric TiO2−x targets. The as deposited films were XRD amorphous and their microstructure was varied by changing the Ar-pressure and the applied dc power during sputtering. An anneal treatment at 673 K/1 h in air resulted in the crystallization of a preferentially oriented anatase phase, the degree of which depended on the deposition conditions. The microstructure, optical and photocatalytic properties of the thin films were investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
43
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 27 publications
3
43
0
1
Order By: Relevance
“…21 In the case of room temperature deposition, yielding initially amorphous films with varying stoichiometry, growth in the <001> direction can be induced by post-deposition heat treatment. 18,20 This textured growth is an intrinsic property of the films and is unaffected by the type of substrate that is used. 18 We have previously demonstrated that the preferential <001> orientation of the crystal grains in nanostructured films can be controlled by altering the partial oxygen pressure in the deposition chamber during thin-film preparation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 In the case of room temperature deposition, yielding initially amorphous films with varying stoichiometry, growth in the <001> direction can be induced by post-deposition heat treatment. 18,20 This textured growth is an intrinsic property of the films and is unaffected by the type of substrate that is used. 18 We have previously demonstrated that the preferential <001> orientation of the crystal grains in nanostructured films can be controlled by altering the partial oxygen pressure in the deposition chamber during thin-film preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that reactive DC magnetron sputtering yields anatase TiO 2 films with preferential orientation along the <001> crystallographic direction. [18][19][20] Depending on the preparation conditions, this orientation might be altered. For example if the films are deposited at high temperature, leading to direct formation of anatase, substrate bias can be used to change the crystallographic orientation.…”
mentioning
confidence: 99%
“…NiO x films have been fabricated by various techniques which include spin coating, dipping, electrochemical deposition [17], magnetron sputtering [18][19][20] and sol-gel [21][22][23][24][25]. With the exception of electrochemical techniques, the other deposition methods require subsequent thermal treatments in order to enhance the density of the coatings [21][22][23][24][25][26], to obtain crystalline structure in the as deposited sputtered coatings [26] and to remove the binder in the case of sol-gel deposited coatings [21][22][23][24][25]. Typically sintering conditions of 300-450 °C for 30 to 60 minutes are reported [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…A small broadening and shifting of this peak is seen in the doped coatings, indicating the distortion of the crystal lattice by these dopants. Heat treatment of TiO2 has been reported to increase its crystallinity and photocatalytic performance [25,32]. The coatings in this work were therefore annealed at 600 C in air to investigate the effect on the structure and properties.…”
Section: Resultsmentioning
confidence: 99%
“…The coatings in this work were therefore annealed at 600 C in air to investigate the effect on the structure and properties. However, an evaluation of the surface topography revealed that heat treatment resulted in the segregation of significant amounts of the co-sputtered material Heat treatment of TiO 2 has been reported to increase its crystallinity and photocatalytic performance [25,32]. The coatings in this work were therefore annealed at 600 • C in air to investigate the effect on the structure and properties.…”
Section: Resultsmentioning
confidence: 99%